Communication Style and Communication Competence Of President Jokowi - Intyaswati, Drina; Juned, Mansur; Zakki Abdullah, Ahmad (International Journal of Engineering and Technology, 2018)
This research would like to see the communication style of president jokowi in connection with the disharmony of his ministers in communicating in public. The problem in this research is; (1) How is President Jokowi's communication style in policy making? (2) How is the communication competency of President Jokowi?. The method used in this research is qualitative by using structural discourse analysis. Data were taken from online news especially detik.com and kompas.com, which is the most popular data provider. The results show that the most widely used communication style of president jokowi is controlling style and also others communication style according to an existing situation. Based on the communication made by the president jokowi, he has communication competence that includes the aspects of commitment and confidence, flexibility, empathy, the sensitivity of consequences, and skills obtained from adaptationÂ Â Â